PEMANFAATAN MEDIA CD UNTUK PEROLEHAN BELAJAR IPA SISWA KELAS VI DI SEKOLAH DASAR TORSINA I SINGKAWANG SELATAN - Polinus, Polinus; Astuti, Indri; Fadillah, Fadillah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThe purpose of this research to determine the preparation design of interactive CD application to acquisition the  science learning on the sixth grade student of elementary school Torsina I south Singkawang.The research will be held in elementary school Torsina I south Singkawang, Singkawang city, using qualitative descriptive approach. the data collection techniques performed in this research were interview, observation and documentation. the data processing techniques used the examination of degree of confidence techniques.The results was found in research are 1. interactive media planning to acquisition the  science learning on the sixth grade student of elementary school Torsina I south Singkawang has been held according with the steps that have established by making the preparation of learning determining the purpose of use CD media, and the benefit of procedures. 2. The teacher have implemented use of CD media with the best of these steps.. 3. The obstacles was found by science teacher in elementary school Torsina I south Singkawang in the benefit of CD media is too low of teachers ability to use computer and media that will be used by teachers are not always available in school.                               Keywords: CD Media, To Improve The Achievement Of Science Learning